2011
DOI: 10.1371/journal.pone.0016718
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Event Assessment of Antimuscarinics for Treating Overactive Bladder: A Network Meta-Analytic Approach

Abstract: BackgroundOveractive bladder (OAB) affects the lives of millions of people worldwide and antimuscarinics are the pharmacological treatment of choice. Meta-analyses of all currently used antimuscarinics for treating OAB found similar efficacy, making the choice dependent on their adverse event profiles. However, conventional meta-analyses often fail to quantify and compare adverse events across different drugs, dosages, formulations, and routes of administration. In addition, the assessment of the broad variety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 88 publications
3
96
0
3
Order By: Relevance
“…This is in accordance with the Guidelines of the European Association of Urology on NLUTD, stating that 'neurogenic patients usually need a higher dose of AM agents than patients with IDO (LE 1b).' 4 In regards to tolerability and safety, the study results demonstrate that oxybutynin IR has the highest dry mouth rate compared with all other AM (Tables 3a and 3b), which is in accordance with the results given in the meta-analyses by Chapple et al 1 and Kessler et al 40 in patients with IDO/OAB. Although many neurogenic Table 3a Placebo-controlled studies-tolerability and safety outcomes a Sto¨hrer et al 13 Sto¨hrer et al 15 Sto¨hrer et al 14 Ethans et al 16 Oxy Table 3b Active-controlled studies-tolerability and safety outcomes a…”
Section: Discussionsupporting
confidence: 88%
“…This is in accordance with the Guidelines of the European Association of Urology on NLUTD, stating that 'neurogenic patients usually need a higher dose of AM agents than patients with IDO (LE 1b).' 4 In regards to tolerability and safety, the study results demonstrate that oxybutynin IR has the highest dry mouth rate compared with all other AM (Tables 3a and 3b), which is in accordance with the results given in the meta-analyses by Chapple et al 1 and Kessler et al 40 in patients with IDO/OAB. Although many neurogenic Table 3a Placebo-controlled studies-tolerability and safety outcomes a Sto¨hrer et al 13 Sto¨hrer et al 15 Sto¨hrer et al 14 Ethans et al 16 Oxy Table 3b Active-controlled studies-tolerability and safety outcomes a…”
Section: Discussionsupporting
confidence: 88%
“…4 Nevertheless, treatment with antimuscarinic drugs is frequently discontinued due to side effects (dry mouth and constipation) or a lack of efficacy. 5 In particular in patients with SCI, who suffer from a neurogenic bowel dysfunction, the concomitant antmiuscarinic treatment will worsen the constipation. Therefore there is a need for therapy alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…There is very little high-quality evidence of a difference between agents in terms of these sideeffects, with only oxybutynin 10mg conferring a significantly increased risk. 10 An analysis of UK prescription data found that the proportion of patients still on their originally prescribed agent at 12 months ranged from 14-35% for different agents in common use. 11 This poor persistence rate is due to a combination of side-effects and lack of perceived efficacy.…”
Section: Pharmacotherapy For Oabmentioning
confidence: 99%